The Experimental Study of the Cerium Dioxide - Silicon Interface of MIS Structures - Л. М. Королевич; О. В. Борисов; А. О. Воронько (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2021)
The article is devoted to the actual task of studying a dielectric, which is an alternative to silicon dioxide in metal-insulator-semiconductor (MIS) structures. In metal-silicon dioxide-silicon structures, upon going to nanosize, the thickness of the dielectric film decreases so much that it becomes tunnel-transparent and its breakdown voltage decreases. These phenomena can be eliminated by replacing silicon dioxide with a dielectric with a higher dielectric constant. These dielectrics primarily include oxides of transition and rare-earth metals. The parameters and characteristics of the MIS structure are determined by various factors, but the properties of the dielectric and the dielectric-semiconductor interface play a special role. In previous works of the authors, it was theoretically proved that cerium dioxide from a number of candidate dielectrics should have the best quality of the interface with silicon. This work is devoted to a study aimed at determining the flat-band voltage and capacitance of MIS structures and at assessing the quality of the cerium dioxide-silicon interface. The study is carried out by the method of capacitance-voltage characteristics. For this, the high-frequency capacitance-voltage characteristics of the aluminum – cerium dioxide – silicon structures were measured at different temperatures. The capacity of the space charge region (SCR) in the enrichment and weak inversion modes of the near-surface layer of a semiconductoris considered. It is shown that the dependence of this capacitance in the (–2) degree on the voltage at the metal electrode cs-2(VG) is linear. The intersection of this line with the abscissa axis makes it possible to determine the flat-band voltage. The slope tangent of this linear dependence makes it possible to determine the energy density of the charge at the dielectric–semiconductor interface. It is shown that the charge density at the cerium dioxide – silicon interface corresponds to the minimum values of the charge density at the silicon dioxide – silicon interface. The absence of a shift in the capacitance-voltage characteristics of the structures under study with a change in temperature indicates the stability of the charge at the cerium dioxide - silicon interface.